2020
DOI: 10.46328/ijonse.19
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Multimedia Instructional Learning Packages in Enhancing Secondary School Students’ Attitudes toward Biology

Abstract: The study investigated the effectiveness of multimedia learning packages in improving the attitudes of students toward learning Biology in secondary schools. The study employed a quantitative and qualitative research approach. The population for the study consisted of all students offering Biology as a subject in the senior secondary schools in Ibadan North Local Government Area of Nigeria, from where a sample of 80 students was randomly selected from three secondary schools and assigned to three groups (one c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 20 publications
3
30
0
3
Order By: Relevance
“…The findings of the study are in line with those of other studies (Akinbadewa & Sofowora, 2020;Akinoǧlu & Tandoǧan, 2007;Koksal & Berberoglu, 2014;Sen & Oskay, 2016, (Akinbadewa & Sofowora, 2020Akinoǧlu & Tandoǧan, 2007;Çepni et al, 2006;Koksal & Berberoglu, 2014;Rabgay, 2018). These studies tested the effect of instructional methods, like technology-based instructions and laboratory methods on students' attitude towards biology, whereby such instructional methods improved students' attitudes towards science, including biology.…”
Section: Discussionsupporting
confidence: 85%
“…The findings of the study are in line with those of other studies (Akinbadewa & Sofowora, 2020;Akinoǧlu & Tandoǧan, 2007;Koksal & Berberoglu, 2014;Sen & Oskay, 2016, (Akinbadewa & Sofowora, 2020Akinoǧlu & Tandoǧan, 2007;Çepni et al, 2006;Koksal & Berberoglu, 2014;Rabgay, 2018). These studies tested the effect of instructional methods, like technology-based instructions and laboratory methods on students' attitude towards biology, whereby such instructional methods improved students' attitudes towards science, including biology.…”
Section: Discussionsupporting
confidence: 85%
“…It is important to understand the impact of distance learning on the effects of education and the social consequences of maintaining this type of education. Many researchers have extensively studied the impact of distance learning on education and have found that distance education has a number of benefits such as ensuring the continuity of education [17,18], ensuring a lifelong learning [19,20], and reducing the high costs associated with traditional education [21]. Limitations such as teaching methods, scheduling, and time have existed since the teacher and the learner were located in different places [22,23].…”
Section: The Impact Of Covid-19 Pandemic On Educationmentioning
confidence: 99%
“…Informal learning will become more important in the future and this informal learning is strongly influenced by communication between peers which is a critical element of distance learning (Cross, 2006, as cited in Auvinen & Smith, 2012. It provides benefits such as reducing education cost (Harrison and Lee, 2018) and ensuring the sustainability of education (Akinbadewa and Sofowora, 2020). Further it helps to provide lifelong learning opportunities for people (Alharthi, 2020).…”
Section: Distance Learning and Online Based Educationmentioning
confidence: 99%